Crystal structure of dense pseudo-cubic boron allotrope, pc-B₅₂, by powder X-ray diffraction - Kurakevych, O.O.; Solozhenko, V.L. (Сверхтвердые материалы, 2013)
During past years, a number of reports have been published on synthesis of tetragonal allotrope of boron, t-B₅₂ phase. However, no unambiguous characterization of the crystal structure has been performed to the present time, while remarkable variation of the a/c lattice-parameter ratio raises strong doubts about its uniqueness. Here the Rietveld refinement of the crystal structure of the high pressure-high temperature boron phase synthesized by a direct solid-state transformation of rhombohedral β-B₁₀₆ at 20 GPa and 2500 K has been reported for the first time. Although this boron allotrope belongs to the t-B₅₂ type, its structure can be considered as pseudo-cubic with the a/c ratio of √2. В останні роки опубліковано ряд повідомлень про синтез тетрагональної алотропної модифікації бору, t-B₅₂. Однак її кристалічну структуру не було однозначно встановлено, а значні відхилення відношення параметрів решітки a/c змушують засумніватися в її єдиності. У цьому повідомленні вперше приведено результати рітвельдівського уточнення кристалічної структури високотемпературної фази високого тиску бору, отриманої прямим твердофазним перетворенням ромбоедричного β-B₁₀₆ при 20 ГПа і 2500 К. Незважаючи на те, що ця фаза належить до типу t-B₅₂, її структуру слід розглядати як псевдокубічну з відношенням a/c рівним √2 . В последние годы опубликован ряд сообщений о синтезе тетрагональной аллотропной модификации бора, t-B₅₂. Однако ее кристаллическая структура не была однозначно установлена, а значительные отклонения отношения параметров решетки a/c заставляют усомниться в ее единственности. В этом сообщении впервые приведены результаты ритвельдовского уточнения кристаллической структуры высокотемпературной фазы высокого давления бора, полученной прямым твердофазным превращением ромбоэдрического β-B₁₀₆ при 20 ГПа и 2500 К. Несмотря на то, что эта фаза принадлежит к типу t-B₅₂, ее структуру следует рассматривать как псевдокубическую с отношением a/c равным √2 .